EFFECTS OF AZOXYSTROBIN AND FLUSILAZOLE ON GROWTH AND PROTEIN AMOUNT OF Scenedesmus acutus - Bedil, Burcin; Kendirlioglu, Gokce; Agirman, Nur; Cetin, A. Kadri (Parlar Scientific Publications (P S P), 2015)
In this study, the effects of azoxystrobin and flusilazole on algae were investigated using Scenedesmus acutus. The green alga was exposed to different concentrations of azoxystrobin and flusilazole (1, 3, 6, 10 and 15 111) in the laboratory, maintained at 23 +/- 1 degrees C and 16:8-h light: dark regime. Cell numbers were determined daily and growth rates were calculated for a period of 4 days. The results showed toxic effects of azoxystrobin and flusilazole on S. acutus on the second day (24 h). In general, the growth rate and protein amount of S. acutus in control cultures treated with azoxystrobin and flusilazole were suddenly decreasing between 2-4 days. In contrast, in all control cultures, the growth rate and protein amount of S. acutus was always positive between 1-4 days. The results of this study indicate that sensitivities to azoxystrobin and flusilazole of S. acutus began in the first day of inoculation, and in this time, the algae decreased in cultures treated with azoxystrobin and flusilazole.
Keywords: Scenedesmus acutus; azoxystrobin; flusilazole; protein amount